NMR-Based Metabolomics Reveals Effects of Water Stress in the Primary and Specialized Metabolisms of Bauhinia ungulata L. (Fabaceae) - Borim de Souza, Ana Júlia [UNESP]; Ocampos, Fernanda Maria Marins; Catoia Pulgrossi, Rafael; Dokkedal, Anne Lígia [UNESP]; Colnago, Luiz Alberto; Cechin, Inês [UNESP]; Saldanha, Luiz Leonardo [UNESP] (MDPI, 2023)
Bauhinia ungulata is a plant used in Brazilian traditional medicine for the treatment of diabetes. Phytochemical studies revealed flavonoids and the saccharide pinitol related to hypoglycemic activity of the Bauhinia species. To determine the effects of water deficit on ecophysiological parameter and metabolite fingerprints of B. ungulata, specimens were treated with the following water regimens under greenhouse conditions: daily watering (control), watering every 7 days (group 7D), and watering every 15 days (group 15D). Metabolite profiling of the plants subjected to water deficit was determined by LC-HRMS/MS. An NMR-based metabolomics approach applied to analyze the extracts revealed increased levels of known osmoprotective and bioactive compounds, such as D-pinitol, in the water deficit groups. Physiological parameters were determined by gas exchange in planta analysis. The results demonstrated a significant decrease in gas exchange under severe drought stress, while biomass production was not significantly different between the control and group 7D under moderate stress. Altogether, the results revealed that primary and specialized/secondary metabolism is affected by long periods of severe water scarcity downregulating the biosynthesis of bioactive metabolites such as pinitol, and the flavonoids quercetin and kaempferol. These results may be useful for guiding agricultural production and standardizing medicinal herb materials of this medicinal plant.
Keywords: D-pinitol; diabetes; flavonoids; pata-de-vaca; water regimes